Perlindungan Konsumen Pada Jasa Pengelola Parkir 24 Jam Atas Hilangnya Kendaraan Bermotor Melalui Mediasi Di Kepolisian Sektor Purwosari (Studi Kasus Parkir 24 Jam Di Purwosari, Bojonegoro) - Rosawati, Nirda Nanda; Kartika, Adhitya Widya (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to find out and understand the legal relationship between parking managers and consumers whose vehicles are lost in parking areas based on the civil law system in Indonesia and to know and understand the responsibility of parking managers for consumers' lost motorized vehicles in parking areas according to Law Number 8 1999 concerning Consumer Protection. With using regulasitive juridical research methods, conclusions can be drawn, namely: 1. The legal relationship between parking managers and consumers is actually a relationship that gives rise to rights and obligations. This relationship is regulated concretely on two main legal bases, namely: First, the Civil Code which regulates in general that the agreement between consumers and parking managers originating from goods custody agreements/agreements; and Second, the Consumer Protection Law which specifically regulates the legal relationship between parking managers and consumers based on the legal position of each party referred to as business actors and consumers. 2. The responsibility of the parking manager for consumer vehicles lost in the parking area based on the Consumer Protection Law is a civil responsibility oriented towards compensation. This is based on: First, the legal obligations of parking managers who must fulfill consumers' rights to comfort, security and maintenance during the use of parking services by consumers, thus giving rise to the responsibility of parking managers if consumers' vehicles are damaged or lost during the process of using these services; Second, the loss of a consumer's vehicle in the parking area gives rise to the consumer's legal right to demand compensation from the parking management before the court in the form of an unlawful act lawsuit even though there is a standard/exanoration clause included on the parking ticket;